2019
DOI: 10.1021/acs.jpcc.9b05689
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest and Guest–Guest Interactions of P- and N-Containing Structure Directing Agents Entrapped inside MFI-Type Zeolite by Multinuclear NMR Spectroscopy

Abstract: Highly crystalline pure silica MFI zeolites have been synthesized using tetraethylammonium (TEA), tetraethylphosphonium (TEP) or a mixture of both cations in different proportions as organic structure directing agents (OSDAs). The zeolites have been deeply characterized in order to get insight about the guest-guest interactions involving the OSDAs and the guesthost interactions involving the OSDAs and the inorganic framework, as well as the main features of the resulting materials. The results show that the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 58 publications
4
20
1
Order By: Relevance
“…It has been established experimentally that MFI_(TEA,F) and MFI_(TPA,F) exhibit dynamic disorder of the uoride anions at room temperature. 19,21,22 Whereas the former system…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established experimentally that MFI_(TEA,F) and MFI_(TPA,F) exhibit dynamic disorder of the uoride anions at room temperature. 19,21,22 Whereas the former system…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, it was also shown that the replacement of tetraethylammonium (TEA) by tetraethylphosphonium (TEP) slows down the uoride motion. 22 Electronic structure calculations in the framework of DFT have been widely used to study zeolite structures and properties. 23 With regard to uoride-containing zeolites, several authors have used DFT methods to investigate the local uoride environment, 16,17,24,25 to predict 19 F NMR shifts or vibrational spectra, 2629 and to study the stability of dierent possible uoride positions.…”
Section: Introductionmentioning
confidence: 99%
“…[44] The full characterization of Ti species in zeolites is essential to understand the detailed property of the Ti active center in heterogeneous catalysis and photocatalysis. 47 Ti/ 49 Ti SSNMR has been applied to uncover the titanium environment of fresh and reused titanium-immobilized mesoporous silica nanoparticles. [45] Additionally, 47,49 Ti SSNMR has been employed to probe the location and chemical environment of Ti in Ti-substituted USY and MFI-type TS-1 zeolites although the spectra featured low resolution because of the low gamma nature and low natural abundance of the NMR-active 47,49 Ti nucleus.…”
Section: Characterization Of Extra-framework Species In Zeolitesmentioning
confidence: 99%
“…47 Ti/ 49 Ti SSNMR has been applied to uncover the titanium environment of fresh and reused titanium-immobilized mesoporous silica nanoparticles. [45] Additionally, 47,49 Ti SSNMR has been employed to probe the location and chemical environment of Ti in Ti-substituted USY and MFI-type TS-1 zeolites although the spectra featured low resolution because of the low gamma nature and low natural abundance of the NMR-active 47,49 Ti nucleus. [46] It was found that Ti in a TS-1 framework was essentially tetrahedrally coordinated and became octahedrally coordinated in the presence of water.…”
Section: Characterization Of Extra-framework Species In Zeolitesmentioning
confidence: 99%
“…These materials exhibit comparable physicochemical properties,asdemonstrated by scanning electron microscope (SEM, Figures S5c-d) as well as MAS 29 Si and 27 Al ssNMR (Figures S6 and S7, Table S3). [47] Importantly,a sshown in Figure 1, qualitative analysis of the diffusion behaviors in zeolite channels using molecular dynamics (MD) simulations exhibited that the channels with short dimensions (SD) were preferentially filled with methanol molecules at the early stage of diffusion, although both channel dimensions were equivalently filled with the molecules eventually (t = t5 in Figure 1). Furthermore,n oa pparent diffusion of the molecules from the SD channels into the channels in long dimensions (LD) was observed ( Figure 1a nd movie S1).…”
Section: Resultsmentioning
confidence: 99%